Implikasi Konteks Perempuan Yahudi dalam Penerapan Gereja Masa Kini - Maria Shintia Kapojos; Randy Frank Rouw; Hengki Wijaya (Sekolah Tinggi Teologi Simpson, 2019)
As people who had chosen by God, Israelites already have a concept about how to treat women in their culture. Laws in Jewish culture had organized the attitude that women must play to preserve life as God's chosen people. This article is wrote using descriptive methods. As a result, in Jewish culture, women’s role was down under men (inferior). However, besides their primary task in their family, as the progress is women join in worship and leadership. This age, women have the same opportunities to involved in it.Sebagai masyarakat yang dipilih Allah, bangsa Israel telah memiliki konsep tentang bagaimana memperlakukan perempuan dalam kebudayaannya. Peraturan-peraturan dalam kebudayaan Yahudi telah mengatur bagaimana sikap yang harus diperankan kaum perempuan dalam memelihara kehidupan sebagai umat pilihan Tuhan. Sebagai kesimpulan, dalam kebudayaan Yahudi, peran perempuan menjadi lebih di bawah dibandingkan pria (inferior). Meskipun demikian, selain tugas utamanya dalam kehidupan keluarga, dalam perkembangannya perempuan terlibat dalam peribadatan dan kepemimpinan. Saat inipun perempuan memiliki kesempatan yang sama untuk terlibat di dalamnya.